Study About Image Capture Device Based on Internet of Things (IoT)Technology - Khairul Imtihan; Wire Bagye; Mohammad Taufan Asri Zaen; Sofiansyah Fadli; Maulana Ashari (Research Developments in Science and Technology Vol. 5, 2022)
Tracing stolen cattle in the NTB province’s Lombok Tengah regency is done by following footprints and waiting at specific locations that are regarded the path to be crossed or the final destination of cattle theft, known as "Ngendeng" Ngendeng is carried out day and night from the time the livestock is declared missing until the livestock is found or the potential to be found is considered lost. The issue with Ngendeng’s operations is that it puts people’s lives in peril if there is a fight with thieves, as well as a decline in health for the inhabitants of Ngendeng. An Internet of Things (IoT) gadget for image capture was designed to replace the community’s function in Ngendeng. The Research and Development (R&D) approach is used in the development of gadgets to create goods and test their effectiveness. The Participatory Rural Appraisal (PRA) approach was utilised to trace the site of deployment of devices in each sub-district. As a result, the most often travelled point (high potential) has been identified for the placement of IoT-based image capture devices in an effort to minimize cattle theft in Lombok Tengah Regency.